Orchidopexy restores morphometric-stereologic changes in the caput epididymis and daily sperm production in cryptorchidic mice, although sperm transit time and fertility parameters remain impaired - Garcia, Patrick Vianna; Arroteia, Kelen Fabiola; Joazeiro, Paulo Pinto; Paccola Mesquita, Suzana de Fatima; Kempinas, Wilma de Grava [UNESP]; Violin Pereira, Luis Antonio (Elsevier B.V., 2011)
Objective: To evaluate the changes in the caput epididymis following cryptorchidism and orchidopexy.Design: Experimental study in a research laboratory.Setting: Reproductive biology research laboratory.Animal(s): Immature male and mature female mice (C57BL/6).Intervention(s): Experimental cryptorchidism and orchidopexy.Main Outcome Measure(s): Morphometric-stereologic analyses, serum testosterone dosage, immunohistochemical staining of the antigen TRA54 (testicular germ cells immunized to a rat monoclonal antibody), smooth muscle alpha-actin (SM alpha-actin) and SM myosin heavy chain, sperm transit time, and fertility parameters.Result(s): There was a significant reduction in the morphometric-stereologic parameters in the cryptorchidic mice. These parameters demonstrated significant recovery following orchidopexy. Staining for an androgen-dependent antigen, TRA54, was observed in all groups. SM alpha-actin and SM myosin heavy chain staining was significantly increased in the cryptorchidism group but stable in the orchidopexy group. Despite the recovery of daily sperm production in the testes, the sperm transit time in the epididymis and fertility parameters remained significantly reduced in the orchidopexy group.Conclusion(s): In cryptorchidic animals, there was an acceleration of sperm passage through the epididymal duct. Orchidopexy did not restore the normal passage time. Accordingly, there was a significant reduction in the fertility parameters in the cryptorchidic group that were not fully recovered following orchidopexy. (Fertil Steril (R) 2011;96:739-44. (C)2011 by American Society for Reproductive Medicine.)
Keywords: Cryptorchidism; orchidopexy; epididymis; sperm; fertility